Effect of the selective dorsal rhizotomy on the clinical presentation and daily care of children with spastic cerebral palsy - Jucá, Renata Viana Brígido de Moura; Jucá, Carlos Eduardo Barros; Caldas, Carla Andrea Tanuri; Ioriatti, Enrico Salomão; Baptista, Cyntia Rogean de Jesus Alves de; Machado, Hélio Rubens (Acta Fisiátrica, 2011)
Spasticity causes various functional and motor impairments for the child, making positioning and hygiene difficult. The study of the association of surgery and physical thera-peutic treatments that provide control of spasticity is of fundamen-tal importance. Objective: To evaluate the impact of selective dorsal rhizotomy (SDR) in the clinical framework of spastic children and the routine of daily care. Methods: The study included seven children with spasticity, 4-5 GMFCS, 5 to 11 years old. Before and after surgery, the following data were evaluated: the degree of spasticity of the adduc-tor muscle groups of the hip and hamstrings in the legs and the elbow flexor group of upper limbs by using a Modified Ashworth Scale, and the measurement of the unilateral and bilateral popliteal angle, the angle of hip abduction and ankle dorsiflexion by using goniometry. In addition, a questionnaire was applied to families to assess the degree of difficulty for the daily care and satisfaction after the SDR. Conclu-sions: Reduction of post-operative spasticity in all muscle groups tested in all patients. There was a significant change in the angle goniometry for bilateral popliteal movement (p <0.05). Of the seven families ques-tioned, six (85.7%) reported improvement of the positioning, feeding, hygiene and easy-to-install orthoses. Thus, SDR appears as an option to medical treatment in the treatment of spasticity in refractory cases in CP children with severe spastic quadriplegia, being able to improve their quality of life and that of their care-givers.